1979
DOI: 10.1177/003072707901000206
|View full text |Cite
|
Sign up to set email alerts
|

Antitranspirants for improvement of water use efficiency of crops

Abstract: The use of antitranspirants may guarantee the establishment of seedlings transplanted under drought conditions or prolong the life of mature plants at sub-optimal moisture levels. Where water is really scarce they can reduce transpiration losses to the extent that irrigation intervals may be extended. Whilst, at present, known antitranspirants are relatively expensive, their use can be justified, for example, to prevent shrinkage in high-value fruits, or where crop survival is threatened.Plants need water; but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…The higher leaf turgor in AT-sprayed WD plants is consistent with the notion that AT film decreases water loss and enables prolonged turgor maintenance under WD conditions (del Amor et al, 2010;Feddema, 1954;Lipe and Skinner, 1979). This is supported by our results on plant water use and those reported in the literature (Das and Raghavendra, 1979;Fuehring and Finkner, 1983). Turgor loss in unsprayed WD plants occurred 2-4 days after drought imposition.…”
Section: At Treatment Maintained Relatively High Leaf Turgor Under Drsupporting
confidence: 93%
See 2 more Smart Citations
“…The higher leaf turgor in AT-sprayed WD plants is consistent with the notion that AT film decreases water loss and enables prolonged turgor maintenance under WD conditions (del Amor et al, 2010;Feddema, 1954;Lipe and Skinner, 1979). This is supported by our results on plant water use and those reported in the literature (Das and Raghavendra, 1979;Fuehring and Finkner, 1983). Turgor loss in unsprayed WD plants occurred 2-4 days after drought imposition.…”
Section: At Treatment Maintained Relatively High Leaf Turgor Under Drsupporting
confidence: 93%
“…This is consistent with the notion that the film from AT restricts transpiration by providing a physical barrier to the stomata, thereby increasing stomatal resistance to water vapour diffusion (Anderson and Kreith, 1978;Das and Raghavendra, 1979;Feddema, 1954). Since stomata regulate both water vapour loss and carbon dioxide intake, a concurrent reduction in photosynthesis was expected.…”
Section: At Reduced Water Loss By Decreasing Transpiration But Maintasupporting
confidence: 86%
See 1 more Smart Citation
“…Recent reviews of methods of improving crop water productivity [1,3,4] have omitted one agronomic method: the use of film antitranspirants to reduce water loss from plants. This omission is understandable, since the three main reviews of antitranspirants [5][6][7] and subsequently textbooks on plant water relations and on drought management [8][9][10] have concluded that film antitranspirants have very limited usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review tabulates the published effects of 23 film antitranspirants in concurrently reducing transpiration and photosynthesis across 13 plant species [7]. Reviews and textbooks have therefore concluded that antitranspirants are only of value for situations where photosynthesis is not important but where reduction in water loss is beneficial [5][6][7][8][9][10]. Most of these uses are on ornamental species, e.g.…”
Section: Introductionmentioning
confidence: 99%